MENAKAR DAYA SAING DAERAH KOTA MAGELANG TAHUN 2020 - Arif Barata Sakti; Mohamad Zaenal Arifin (Jendela Inovasi Daerah, 2021)
The higher the level of competitiveness of an area, the higher the level of community welfare. Each region has a different response in mitigating the impact of globalization at this time. The readiness of regions in responding to global challenges will greatly determine the bargaining position of each region in the arena of increasingly fierce global competition. Therefore, writing this article aims to analyze the Regional Competitiveness Index (IDSD) of Magelang Municipality in 2020 as a form of mitigating the impact of globalization. The method developed in writing this article is a descriptive qualitative index value that has been measured by the Ministry of Research and Technology / National Agency for Research and Technology. The findings of this study indicate that the enabling environment is the strongest aspect and the market aspect is the weakest. Furthermore, the results of the mapping of the regional competitiveness index and analysis of its results can be used as a reference in making regional development policies.